Three-dimensional imaging of the S-velocity structure for the crust and the upper mantle beneath the Arabian Sea from Rayleigh wave analysis - Corchete, V. (International journal of earth sciences : Geologische Rundschau, 2017)
A 3D imaging of S-velocity for the Arabian Sea crust and upper mantle structure is presented in this paper, determined by means of Rayleigh wave analysis, for depths ranging from zero to 300 km. The crust and upper mantle structure of this region of the earth never has been the subject of a surface wave tomography survey. The Moho map performed in the present study is a new result, in which a crustal thickening beneath the Arabian Fan sediments can be observed. This crustal thickening can be interpreted as a quasi-continental oceanic transitional structure. A crustal thickness of up to 20 km also can be observed for the Murray Ridge system in this Moho map. This crustal thickening can be due to that the Murray Ridge System consists of Indian continental crust. This continental crust is extremely thinned to the southwest of this region, as shown in this Moho map. This area can be interpreted as oceanic in origin. In the depth range from 30 to 60 km, the S-velocity presents its lower values at the Carlsberg Ridge region, because it is the younger region of the study area. In the depth range from 60 to 105 km of depth, the S-velocity pattern is very similar to that shown for the previous depth range, except for the regions in which the asthenosphere is reached, for these regions appear a low S-velocity pattern. The lithosphere–asthenosphere boundary (LAB), or equivalently the lithosphere thickness, determined in the present study is also a new result, in which the lithosphere thickness for the Arabian Fan can be estimated in 60–70 km. The lower lithospheric thickness observed in the LAB map, for the Arabian Fan, shows that this region may be in the transition zone between continental and oceanic structure. Finally, a low-velocity zone (LVZ) has been determined, for the whole study area, located between the LAB and the boundary of the asthenosphere base (or equivalently the lithosphere–asthenosphere system thickness). The asthenosphere-base map calculated in the present study is also a new result.